Persepsi Akuntan Pendidik terhadap Konsep Dasar, Pengukuran dan Pengungkapan Akuntansi Lingkungan - Devina Rizchy Sari; Paskah Ika Nugroho (Universitas Kristen Maranatha, 2017)
Abstract The object of this study is teaching accountants who are in Salatiga, Surakarta and Semarang. The purpose of this study was to describe the perceptions of teaching accountants to basic concepts, measurement and disclosure of environmental accounting. This study uses 50 respondents who come from the city of Salatiga is 9 teaching accountant from Satya Wacana Christian University, 1 teaching accountant from Islamic Institute, Salatiga and 4 teaching accountant from STIE AMA Salatiga, 27 teaching accountants at the University of March Surakarta and 9 teaching accountants at the University of Dian Nuswantoro Semarang selected through convinience sampling techniques. The analysis used in this study using a frequency average and standard deviation of each of the respondents. The results of this study are teaching accountants assume that the basic concepts of environmental accounting in Indonesia are still on, the costs associated with the cost of environmental activities can be measured in monetary terms and costs associated with the activity of environmental costs should be disclosed in the financial statements. Keywords: Perception; Conceptual of Enviromental Accounting; Measurement of Enviromental Accounting; Disclosure of Enviromental Accounting.